Дослідження архітектури майбутнього викладачами і студентами Придніпровської державної академії будівництва та архітектури - Товстик, Т. М.; Лівертовська, Є. В.; Терно, Ю. В.; Шумінова, Н. В.; Tovstyk, T. M.; Livertovskaya, E. V.; Terno, Y. V.; Shuminova, N. V. (Видавництво Львівської політехніки, 2019)
Розглянуто особливості дослідження архітектури майбутнього, яке здійснюють викладачі та студенти Придніпровської державної академії будівництва та архітектури.

Possibilities of designing kinetic facades in Dnipro to create a comfortable urban environment in accordance with the needs of modern people. The author presents the development of kinetic facades and systems that give a different view of the boundaries of the building, the connection of interior and exterior space. The problems and prospects of industrial park in Dnipro are considered. Typological and functional features of technoparks are classified. Listed modern innovative technologies in architecture. Functional zones of technoparks are compared with the use of various newest technologies in their structure. In this article the concept of multisensory design is analyzed, the possibilities of humanizing the architecture of public institutions and spaces with the help of multisensory design are considered. Examples of the use of multisensory design in public spaces architecture in Ukraine and abroad are given.
Research of architecture future teachers and students of the Pridnipro State Academy of Civil Engineering and Architecture
Keywords: кінетична архітектура; міське середовище; динамічні фасади; інноваційні технології; індустріальний технопарк; мультисенсорний дизайн; гуманізація; громадські простори; принципи мультисенсорного дизайну; kinetic architecture; urban environment; dynamic facades; innovative technologies; industrial technopark; multisensory design; humanization; public spaces; principles of multisensory design